HPV-16 E6/E7 DNA tattoo vaccination using genetically optimized vaccines elicit clinical and immunological responses in patients with usual vulvar intraepithelial neoplasia (uVIN): a phase I/II clinical trial. Issue 8 (2nd August 2021) - Bakker, Noor Alida Maria; Rotman, Jossie; van Beurden, Marc; Zijlmans, Henry J MAA; van Ruiten, Maartje; Samuels, Sanne; Nuijen, Bastiaan; Beijnen, Jos; De Visser, Karin; Haanen, John; Schumacher, Ton; de Gruijl, Tanja D; et al.
Abstract : Background: Usual vulvar intraepithelial neoplasia (uVIN) is a premalignancy caused by persistent infection with high-risk types of human papillomavirus (HPV), mainly type 16. Even though different treatment modalities are available (eg, surgical excision, laser evaporation or topical application of imiquimod), these treatments can be mutilating, patients often have recurrences and 2%–8% of patients develop vulvar carcinoma. Therefore, immunotherapeutic strategies targeting the pivotal oncogenic HPV proteins E6 and E7 are being explored to repress carcinogenesis. Method: In this phase I/II clinical trial, 14 patients with HPV16+ uVIN were treated with a genetically enhanced DNA vaccine targeting E6 and E7. Safety, clinical responses and immunogenicity were assessed. Patients received four intradermal HPV-16 E6/E7 DNA tattoo vaccinations, with a 2-week interval, alternating between both upper legs. Biopsies of the uVIN lesions were taken at screening and +3 months after last vaccination. Digital photography of the vulva was performed at every check-up until 12 months of follow-up for measurement of the lesions. HPV16-specific T-cell responses were measured in blood over time in ex vivo reactivity assays. Results: Vaccinations were well tolerated, although one grade 3 suspected unexpected serious adverse reaction was observed. Clinical responses were observed in 6/14 (43%) patients, with 2 complete responses and 4 partial responses (PR). 5/14 patients showed HPV-specific T-cell responses in blood, measured in ex vivo reactivity assays. Notably, all five patients with HPV-specific T-cell responses had a clinical response. Conclusions: Our results indicate that HPV-16 E6/E7 DNA tattoo vaccination is a biologically active and safe treatment strategy in patients with uVIN, and suggest that T-cell reactivity against the HPV oncogenes is associated with clinical benefit. Trial registration number: NTR4607.